2009
DOI: 10.1371/journal.ppat.1000405
|View full text |Cite
|
Sign up to set email alerts
|

Differential Modulation of TNF-α–Induced Apoptosis by Neisseria meningitidis

Abstract: Infections by Neisseria meningitidis show duality between frequent asymptomatic carriage and occasional life-threatening disease. Bacterial and host factors involved in this balance are not fully understood. Cytopathic effects and cell damage may prelude to pathogenesis of isolates belonging to hyper-invasive lineages. We aimed to analyze cell–bacteria interactions using both pathogenic and carriage meningococcal isolates. Several pathogenic isolates of the ST-11 clonal complex and carriage isolates were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 68 publications
(79 reference statements)
2
58
1
Order By: Relevance
“…Some examples of bacteria that inhibit apoptosis are Chlamydia (20,22,79), Shigella flexneri (11), Brucella (28), Porphyromonas gingivalis (56,58), Neisseria meningitidis, and Neisseria gonorrhoeae (4,23,31,42,50,55,62,65,73). Our group and other workers have reported that live N. meningitidis and purified meningococcal porin inhibit apoptosis (15,49,50,62,75), potentially via multiple mechanisms. While meningococcal infection induces NF-B-mediated upregulation of antiapoptotic genes, purified PorB and PorB from live bacteria directly interact with mitochondria and modulate their membrane potential, preventing release of cytochrome c. N. gonorrhoeae and purified gonococcal porin PIB induce NF-B-mediated upregulation of antiapoptotic genes (4,5,23,33,55,65), which could also contribute to prevention of apoptosis.…”
mentioning
confidence: 84%
“…Some examples of bacteria that inhibit apoptosis are Chlamydia (20,22,79), Shigella flexneri (11), Brucella (28), Porphyromonas gingivalis (56,58), Neisseria meningitidis, and Neisseria gonorrhoeae (4,23,31,42,50,55,62,65,73). Our group and other workers have reported that live N. meningitidis and purified meningococcal porin inhibit apoptosis (15,49,50,62,75), potentially via multiple mechanisms. While meningococcal infection induces NF-B-mediated upregulation of antiapoptotic genes, purified PorB and PorB from live bacteria directly interact with mitochondria and modulate their membrane potential, preventing release of cytochrome c. N. gonorrhoeae and purified gonococcal porin PIB induce NF-B-mediated upregulation of antiapoptotic genes (4,5,23,33,55,65), which could also contribute to prevention of apoptosis.…”
mentioning
confidence: 84%
“…We also show that PMNs can be a significant source of proinflammatory cytokines and chemokines during infection, in addition to the epithelial cells which are thought to be responsible for initial PMN recruitment. Numerous studies of epithelial cells and lymphocytes have shown both pro-and antiapoptotic effects of infection with both N. gonorrhoeae (6,27,36,39,40,50,51) and the closely related N. meningitidis (17,48). However, PMN apoptosis during N. gonorrhoeae infection has not been examined as extensively (68), and it has not been explored at all with N. meningitidis.…”
Section: Discussionmentioning
confidence: 99%
“…Gonococcal infection has also been shown to exert a delaying effect on spontaneous PMN apoptosis during ex vivo infection (68). While the mechanisms by which N. gonorrhoeae manipulates apoptotic signaling in epithelial cells and lymphocytes have been extensively studied (6,17,27,36,40,48,50,51), whether bacterial infection acts on the same signaling pathways in the context of PMNs is less well defined. Several other microorganisms have been shown to influence PMN survival in either a pro-or antiapoptotic manner; in particular, pathogens such as Anaplasma phagocytophilum and Chlamydia trachomatis, which reside and replicate within PMNs, have evolved mechanisms to actively delay PMN apoptosis in order to allow sufficient time to complete their replicative cycles (29,71).…”
mentioning
confidence: 99%
“…The TNFR1 ectodomains released in the extracellular space chelate sTNF-α, providing negative feedback to the TNF-α-induced inflammatory loop (13). Pathogenic bacteria, including Chlamydia trachomatis, Neisseria meningitides, and Staphylococcus aureus, have evolved TNFR1 shedding mechanisms as a strategy for circumventing the host immune response (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%